2023
DOI: 10.1101/2023.01.13.523995
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biophysical modeling with variational autoencoders for bimodal, single-cell RNA sequencing data

Abstract: We motivate and present biVI, which combines the variational autoencoder framework of scVI with biophysically motivated, bivariate models for nascent and mature RNA distributions. In simulated benchmarking, biVI accurately recapitulates key properties of interest, including cell type structure, parameter values, and copy number distributions. In biological datasets, biVI provides a route for the identification of the biophysical mechanisms underlying differential expression. The analytical approach outlines a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…However, mechanistic models can systematically take the experimental design into account and combine multiple types of data such as single-cell, bulk, temporal and perturbation gene expression data. Indeed, a very promising area of future work is harnessing the information contained in the multi-modal single-cell data using inference based on mechanistic models [7,19,49].…”
Section: Discussionmentioning
confidence: 99%
“…However, mechanistic models can systematically take the experimental design into account and combine multiple types of data such as single-cell, bulk, temporal and perturbation gene expression data. Indeed, a very promising area of future work is harnessing the information contained in the multi-modal single-cell data using inference based on mechanistic models [7,19,49].…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that mechanistic models can be used to overcome the challenge of technical noise across modalities commonly suffered by multi-view statistical methods [75, 76]. Data integration across conditions, time and modalities is an important challenge for single-cell multi-omics, including epigenome and proteome [7779], and mechanistic models like ours could provide a versatile tool for integrating these data [80].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these approaches can greatly reduce the amount of time necessary to explore steady-state distributions across a wide range of transcriptional parameters for inference, parameter sensitivity investigations, and experimental design [37]. In particular, we have recently employed KWR application in a popular variational autoencoder framework to infer biophysical parameters for thousands of cells and genes, made possible because KWR, unlike generating function solutions, is compatible with gradient descent algorithms [21,27].…”
Section: Discussionmentioning
confidence: 99%